Gambaran Pengetahuan dan Sikap Masyarakat tentang HIV/AIDS - Guling Setiawan (Syntax Idea, 2021)
This study aims to provide an overview of public knowledge and attitudes about HIV/AIDS in RW.06, RW.07 and RW.15 Kel. Tamansari Area Puskesmas Salam Bandung. This research uses quantitative descriptive design. The subject of this study was people aged between 15-49 years old who were in three RW Tamansari Village, Salam Bandung Health Center Area. The population in this study is the entire community of Tamansari Village, Salam Bandung Health Center Area. Sampling techniques in this study with stratified random sampling techniques with a sample of 97 people. Statistical analysis used in this study is by summing up and then presented. The results showed that the knowledge of people categorized as having less knowledge as much as 40.2%, simply does not exist (0%), and has good knowledge as much as 59.8%. As for the attitude of the community that is categorized as having an un-supportive attitude (-) as much as 46.4% and categorized as having a supportive attitude (+) as much as 53.6%. Based on the results of the research, to be able to improve the knowledge and attitudes of the public is recommended by health officials to provide more information or counseling to the public, so that it is expected that the information received is easier to understand and implement.